2017
DOI: 10.1515/med-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Bone tunnel impaction reduced the tibial tunnel enlargement

Abstract: AbstractThe purpose of this study was to investigate whether the bone tunnel impaction technique performed by dilators could dwindle the tibial tunnel enlargement after anterior cruciate ligament (ACL) reconstruction with hamstring tendon using both extracortical suspensory fixation devices at femoral and tibial site.Thirty-one consecutive patients undergoing primary ACL reconstruction with the hamstring autograft were enrolled in this research. Patients were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Differences in Lysholm scores reported in two studies were not statistically significant both preoperatively (ED: 51.9; SD: 50.1) and postoperatively (ED: 91.7; SD: 93.4). There were no statistically significant differences in Tegner scores reported in one of the studies both preoperatively (ED: 3.5; SD: 3.5) and postoperatively (ED: 6.0; SD: 6.13)(10). Two studies reported no statistically significant differences in IKDC scores preoperatively (ED: 48.6; SD: 49.1) and postoperatively (ED: 92.5; SD: 92.9)(10,16).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Differences in Lysholm scores reported in two studies were not statistically significant both preoperatively (ED: 51.9; SD: 50.1) and postoperatively (ED: 91.7; SD: 93.4). There were no statistically significant differences in Tegner scores reported in one of the studies both preoperatively (ED: 3.5; SD: 3.5) and postoperatively (ED: 6.0; SD: 6.13)(10). Two studies reported no statistically significant differences in IKDC scores preoperatively (ED: 48.6; SD: 49.1) and postoperatively (ED: 92.5; SD: 92.9)(10,16).…”
Section: Resultsmentioning
confidence: 90%
“…There were no statistically significant differences in Tegner scores reported in one of the studies both preoperatively (ED: 3.5; SD: 3.5) and postoperatively (ED: 6.0; SD: 6.13)(10). Two studies reported no statistically significant differences in IKDC scores preoperatively (ED: 48.6; SD: 49.1) and postoperatively (ED: 92.5; SD: 92.9)(10,16). Overall, no statistically significant differences in knee function assays were observed across the clinical studies reviewed.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…If the gap becomes too large, non-union or delayed union may happen even with enough fixation. The gap may be reduced at the tunnel entrance by redirecting the force applies to the graft [25].…”
Section: Discussionmentioning
confidence: 99%